Color atlas of farm animal dermatology. - Scott, Danny W. (Hoboken, New Jersey Wiley-Blackwell, 2018)
"Color Atlas of Farm Animal Dermatology, Second Edition is an essential reference for veterinary dermatologists, practitioners, and students alike. Emphasizing recognition and diagnosis, the book combines hundreds of color photographs with clear and concise text highlighting clinical features, differentials, and diagnostic information for each disease. Coverage includes both common and uncommon diseases of cattle, goats, sheep, llamas and alpacas, and pigs. This new edition has been fully updated throughout, and now includes information on llamas and alpacas. Diseases covered include bacterial, fungal, parasitic, viral and protozoal, immunological, congenital and hereditary, environmental, nutritional and miscellaneous diseases, as well as neoplastic and non-neoplastic growths. Offers a practical quick reference to aid in the diagnosis of dermatological conditions in farm animals, including cattle, goats, sheep, pigs, alpacas, and llamas. Contains more than 700 full-color images. Covers all dermatological disease types, organized by species-specific sections"--
Contents; Section 1: Bovine; Section 2: Caprine; Section 3: Ovine; Section 4: Porcine; Section 5: Camelid; Index
UP System perpetual contents
Includes bibliographical references and index
Keywords: Livestock -- Diseases -- Atlases; Skin -- Diseases -- Atlases; Veterinary dermatology -- Atlases; Domestic animals